Cross-cultural understanding through visual representation - Beckman, Kristina; Smith, Susan (Colombian Applied Linguistics Journal, 2006)
This article analyzes international students’ drawings of their home countries’ essay assignments. These English as a Second Language (ESL) students often have difficulty in meeting the local demands of our Writing Program, which centers on argumentative writing with thesis and support. Any part of an essay deemed irrelevant is censured as “off topic;” some students see this structure as too direct or even impolite. While not all students found visual representation easy, the drawings reveal some basic assumptions about writing embodied in their native cultures’ assignments. We discuss the drawings first for visual rhetorical content, then in the students’ own terms. Last, we consider how our own pedagogy has been shaped.